A Bibliometric Analysis of Public Policy Trend in 2013-2023 - Suandi, Suandi; Juliartha, Edwar (Indonesian Association for Public Administration (IAPA), 2024)
Public policy not only describes the process and consequences but also a set of tools and general mechanisms that provide choices of actions to be made. Previous research shows that systematic analysis of the current state of public policy is still limited. For this reason, it is necessary public policy mapping research is needed. This research uses a bibliometric approach with Scopus data between 2013 and 2023. The analysis was conducted on 12422 publications. Bibliometrics in this study used Biblioshiny and Vosviewer. The results showed that research on public policy has increased and decreased quite significantly. From 2013 to 2021 there was an increase in publications, but from 2022 to 2023 there was a decrease in publications. The average citations from 2013 to 2023 have increased and decreased. The most visible decrease occurred in 2022, namely by 1.8. The average citation per writing is 20.08. In addition, from the results of Vosviewer, it can also be seen that public administration issues continue to develop and have a network with other issues. Issues that still need to be developed related to covid-19, urban areas, education, epidemiology, social media, mental health, sustainable development, climate change, city policy, child protection policies, and pregnancy.